Transgenerational epigenetics in substance abuse: exploring the inheritable DNA methylation underlying the agressive behaviour and altered stress response. / Professor Dr Teh Lay Kek, Professor Dr Mohd Zaki Salleh and Dr. Richard Muhammad Johari James - Lay Kek, Teh; Salleh, Mohd Zaki; James, Richard Muhammad Johari (Research Management Institute (RMI), 2016)
Addiction is defined as a chronic, relapsing disease that is characterized by (1) compulsive behaviour to seek and take drug, (2) loss of control due to limited intake (3) emergence of negative emotional states (e.g., dysphoria, anxiety, irritability) when access to the drug is prevented (Koob and Le Moal, 1997). Addictive behaviours include a complex variety of symptoms, including loss of control over its use, compulsive use, continued use despite negative consequences, and drug cravings. Of the 20.5 million Americans 12 or older that had a substance use disorder in 2015, 2 million had a substance use disorder involving prescription pain relievers and 591,000 had a substance use disorder involving heroin (Center for Behavioral Health Statistics and Quality, 2016). It is estimated that 23% of individuals who use heroin develop opioid addiction (National Institute on Drug Abuse, 2014; Centers for Disease Control and Prevention, 2016). It is also a chronic relapsing disorder characterized by cycles of escalating drug exposure, intermittent episodes of withdrawal with or without maintained abstinence, and acute or chronic relapse to drug use. Heroin and morphine are more widely used than any other illicit opioids with 13,852 users in Malaysia alone. The profile of drug users detected in 2015 recorded that 97.97% of the addicts are male (Statistics of Drug Users in Malaysia, 2015). Psychiatric comorbidity is commonly found among individuals with addictive disorders. The addicted patients often suffer from anxiety disorders. Hodgson and colleagues (2016) has confirmed the shared genetic underpinnings of addiction and anxiety. Genomic loci that involved in the etiology of the comorbid disorders were found to be heritable. However, a phenotypical study on this inheritance was not yet studied. The association between heroin use and crime has been widely documented. Researchers have consistently found that a large proportion of the heroin-dependent population regularly engage in criminal activity (Inciardi and Chambers, 1972; Voss and Stephens, 1973). Kokkevi et al. (1993), for example, reported that 79% of a small community of heroin-dependent individuals had been arrested and 60% had been convicted for a criminal offence. Recurrent cycles of heroin use and abstinence are thought to cause neurobiological changes in brain regions associated with reward, motivation, stress, learning and executive function (Jentsch and Taylor 1999; Koob and Le Moal 2008; Kreek et al. 2009a,b; Le Merrer et al. 2009; Winstanley et al. 2010). Such changes are thought to persist across extended drug-free periods to alter an individual's response to drug re-exposure and contribute to subsequent escalation of drug use (i.e., relapse-like behaviour) (Dalley et al. 2005).